Inotropic myocardial function dynamics in patients with recurrent atrial fibrillation - N. E. Gaidamakina; L. M. Kunnova; A. I. Tarzimanova; A. V. Vetluzhsky; I. G. Fomina (Кардиоваскулярная терапия и профилактика)
Aim. To study inotropic myocardial function of left and right ventriculum (LV, RV) in patients with recurrent atrial fibrillation (AF), according to balanced radionuclide ventriculography (BRVG) data. Material and methods. The study included 72 patients: 30 individuals with coronary heart disease (CHD) and recurrent AF (Group I), as well as 42 CHD patients without cardiac arrhythmias (Group II). Participants’ age varied from 39 to 79 years (mean age 60.3±2.5 years). To assess systolic and diastolic LV and RV function, all participants underwent BRVG. Results. LV and RV ejection fraction was normal in all subjects. LV peak filling velocity was significantly reduced in patients with recurrent AF, comparing to arrhythmia-free individuals (p<0.05). LV end-diastolic volume in Group I was substantially lower than in Group II (p<0.05). At echocardiography, left and right atrium sizes were increased in patients with recurrent AF. Conclusion. Heart remodeling in patients with recurrent AF manifested by diastolic LV and RV dysfunction, combined with atrium size increase.